(untitled) (Journal of the College of Basic Education, 2026)
This research examines the rhetorical approaches in Abd al-Qahir al-Jurjani’s "Al-Risalah al-Shafiyah," in which he explores the sublimity of the Qur’an and its exalted status in eloquence, asserting its enduring miraculous nature. This treatise holds paramount importance in the field of Qur’anic inimitability. It represents a crucial link in al-Jurjani’s chain of theoretical works, grounded in the merits of its structure and the rational arguments it employs. It highlights the persuasive power and argumentative logic within the treatise, as well as refuting the Mu’tazilite doctrine of "sarfa" (the doctrine that the Qur’an’s inimitability was not established). This research aims to reveal the influential rhetorical approaches and structural foundations of his discourse, enabling him to address human intellects effectively and dispel doubt and uncertainty.